Pengaruh p-Klorofenol terhadap Efektivitas Fotoreduksi Ion Hg(II) yang Dikatalisis TiO2 - Devina Ingrid Anggraini; Endang Tri Wahyuni; Mudasir Mudasir (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2008)
The objective is to develop photoreduction method catalyzed by TiO2 for the decreasing Hg(II) concentration. Photocatalytic reduction was carried out in a closed reactor equipped with UV lamp, by irradiating and stirring a mixture of Hg(II) solution and TiO2 photocatalyst powder for a certain period of time. The amount of reduced Hg(II) by photoreduction was calculated by substracting initial Hg(II) concentration with unreduced one, which was determined using cold vapor atomic absorption spectrophotometry method. The result of the research indicated that the use of TiO2 photocatalyst has increased the effectiveness of Hg(II) photoreduction. In the photocatalysis process TiO2 exposured by photon energy could resulted in •OH radicals and electrons that can recombined in the same time. The presence of p-chlorophenol in the solution mixture increased the photoreduction effectiveness probably due to its capability in capturing •OH radicals.TiO2 decreases in its crystalinity up to 15.54 % after process.Keywords: photoreduction, Hg(II), TiO2, p-chlorophenol